Do vivido ao escrito : o testemunho de Lima Barreto em Diário do hospício e O cemitério dos vivos - Silva, Cinthia Mara Cecato da (2017)
This argumentative text proposes to instigate reflections that approximate the literary production of the Carioca writer Lima Barreto (1881-1922) to literature with a testimonial content. Analyzing the plot of the works that had the floor of the asylum, Diário do Hospício (2010) and O cemitério dos vivos (2010), we tried to investigate four essential aspects to strengthen the arguments made. They are: hospice, madness, asylum practices and, finally, testimony. Agglutinated – as in a "web? – they aim to support the hypotheses raised, qualifying the Brazilian psychiatric system of old as inefficient, since it functioned - despite the initial intentions of improvement - much more as a practice of elite domination determined to give visibility to "doctor status," than a mental health institution capable of treating "madness." For the development of this research, which sees exposed collective fractures overlapping a literature exclusively of itself, there was a determined selection of scholars, such as: Michel Foucault, Pierre Bourdieu, Márcio Seligmann-Silva, Beatriz Resende, Antonio Arnoni Prado, Roberto Vecchi, Lilia Moritz Schwarcz, among others. Full references to the arguments, all in their way, allowed to find intersections that lead to a point in Lima Barreto: between what was lived and what was written, there are traces that need to be recovered, albeit literarily, in honor of the then guests of the defunct Hospital Nacional de Alienados.